Integrative multi-omics and Mendelian randomization analysis reveal SPP1+ tumor-associated macrophage-driven prognostic signature for hepatocellular carcinoma - Lei, Kai; Lei, Yichun; Wang, Zeyao; Ye, Zhixin; Liu, Jiawei; Chen, Wenhao; Zhou, Caihong; Tan, Jinmei; Chen, Shuxian; Zhang, Yifan; Tan, Jiehui (Frontiers in Molecular Biosciences, 2025)
BackgroundThe SPP1+ tumor-associated macrophages (TAMs) have been implicated in tumor metastasis and immune evasion. However, the prognostic significance of SPP1+ TAMs in hepatocellular carcinoma (HCC) remains largely unexplored. This study aimed to identify SPP1+ TAMs-related genes and construct a model to predict overall survival (OS) in HCC patients.MethodsSingle-cell RNA sequencing (scRNA-seq) datasets from HCC patients were analyzed to identify SPP1+ TAMs. SPP1+ TAMs-related risk score (STRS) was developed using Mendelian randomization (MR) analysis and Least Absolute Shrinkage and Selection Operator (LASSO) regression. HCC patients from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) cohorts were stratified into high- and low-STRS groups based on STRS. Kaplan-Meier survival analysis, receiver operating characteristic (ROC) curve analysis, and functional enrichment analysis were performed to assess the prognostic value of STRS.ResultsSPP1+ TAMs exhibited strong associations with immunosuppressive functions. 16 SPP1+ TAMs-related genes were used to construct STRS. Patients in the high-STRS group had significantly worse OS than those in the low-STRS group (p < 0.001). ROC analysis demonstrated robust predictive power, with AUC values ranging from 0.685 to 0.748 for 1-year OS, 0.717 to 0.739 for 2-year OS, and 0.719 to 0.738 for 3-year OS. The STRS model also exhibited strong predictive capability for the distinction of drug resistance.ConclusionThis study identified SPP1+ TAMs-related genes as key prognostic indicators in HCC. The STRS model provides an effective tool for predicting patient survival and may facilitate personalized treatment strategies for HCC. These findings enhance the understanding of TAMs-driven immune modulation in HCC and highlight potential therapeutic targets for improving patient outcomes.